2022
DOI: 10.3389/fgene.2022.922358
|View full text |Cite
|
Sign up to set email alerts
|

A Novel M7G-Related MicroRNAs Risk Signature Predicts the Prognosis and Tumor Microenvironment of Kidney Renal Clear Cell Carcinoma

Abstract: Background: M7G modification is extremely vital for the development of many cancers, especially tumor immunity. M7G modification is a novel functional regulator of miRNA, and the researches on m7G-related miRNAs in kidney renal clear cell carcinoma (KIRC) are still insufficient. This research aims to establish a risk signature on the foundation of m7G-associated miRNAs, which can precisely forecast the prognosis of KIRC patients.Methods: Transcriptome data and clinical data used in this study come from The Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Based on their functions in biological processes, m7G-related genes are classified into three types: writers (methyltransferases), readers (binding proteins), and erasers (demethylases) [ 3 , 7 , 8 ]. In human beings, methyltransferase-like 1 (METTL1) and the WD repeat domain 4 (WDR4) are the most well-studied regulators of m7G, and have been reported to participate in tumor progression by regulating tumor immunity, metabolic reprogramming, and drug resistance [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their functions in biological processes, m7G-related genes are classified into three types: writers (methyltransferases), readers (binding proteins), and erasers (demethylases) [ 3 , 7 , 8 ]. In human beings, methyltransferase-like 1 (METTL1) and the WD repeat domain 4 (WDR4) are the most well-studied regulators of m7G, and have been reported to participate in tumor progression by regulating tumor immunity, metabolic reprogramming, and drug resistance [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Liu et al [ 20 ] also identified the prognostic value of m7G-related lncRNAs in prostate cancer. Moreover, three studies demonstrated the prognostic value of m7G-related mRNAs, lncRNAs, and miRNAs in clear cell renal cell carcinoma [ 16 18 ]. Furthermore, we also assessed the prognostic value of the risk score in various subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 15 ] identified m7G-related clusters that could predict the prognosis of hepatocellular carcinoma patients. Furthermore, in the field of urological tumors, three studies demonstrated the prognostic value of m7G-related mRNAs, lncRNAs and miRNAs in clear cell renal cell carcinoma [ 16 18 ]. Meanwhile, M7G-related genes could influence the immune infiltration of prostate cancer [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, METTL1, a m7G methyltransferase, its aberrant upregulation in tumors has been found to be linked to end-stage tumors and worse prognosis, and METTL1 can drive oncogenic transformation and accelerate tumor progression by promoting m7G tRNA modification (Chen et al, 2021;Ma et al, 2021;Orellana et al, 2021). Notably, recent studies have uncovered that risk models based on m7G-associated miRNA and lncRNAs have potential value in predicting tumor prognosis and immunotherapy outcomes (Hong et al, 2022;Zhang et al, 2022). However, the potential of m7G regulators to serve as predictive biomarkers of prognosis and immunotherapy response across cancers remains unclear.…”
Section: Introductionmentioning
confidence: 99%